The Effect of Patient Acuity Tool on Patient Clinical Practicum Assignments on Nursing Student Satisfaction Levels: A Quasi-Experimental Study - Marionne Leigh V. David; Reeanz Arvin V. Bano; Eric Ferdinand S. Joven; Noel Robertino Manansala; Michaella G. Sta. Ana; Ria Valerie D. Cabanes; Mildred G. Glinoga (Faculty of Nursing Universitas Padjadjaran, 2021)
Background: Unequal patient assignment is a problem of nursing students during clinical practicum. Registered nurses use patient acuity to ensure balanced work distribution, but its benefits has not been assessed on student nurses to date. Purpose: The study’s objective is to determine the effect of patient acuity tool on student nurses’ satisfaction level during practicum. Methods: The study utilized quasi-experimental design to level II and III nursing students at a University in Quezon City, Philippines. 6-Module Online course including videos, notes, and quiz using Google Classroom was used; orientation and simulation were conducted through Zoom and Facebook Messenger. The participants were tasked randomly to use Patient Acuity Tool or conventional method during patient distribution. A modified Kuopio University Hospital Job Satisfaction Scale was used to identify and compare satisfaction levels of the two groups. Descriptive and Independent Samples T-test using Statistical Package for the Social Sciences version 26 were used to analyze data. Results: Requiring factors, motivating factors, and working welfare of students utilizing Patient Acuity Tool are higher in overall mean satisfaction rate (3.36, 3.71, 3.89 vs 3.57, 3.81, 3.91); however, mean satisfaction showed no significant difference based on indicators (p-value 0.372, 0.694, 0.052, 0.921, and 0.469) and overall satisfaction (p-value 0.947). The requiring factors of work reflects the lowest mean scores given by those who have used the Conventional Method focusing on number of staff (2.97) and even workload distribution (2.14). Conclusion: Contrary to the last result, those who have distributed patients using the Patient Acuity Tools gave a mean score of 3.55.